Tipologi Kepemimpinan Kepala Sekolah dalam Pembentukan Karakter Cinta Damai Siswa SMP Piri 1 Yogyakarta - Syaefudin, Syaefudin; Santoso, Sedya (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2018)
This research was conducted because of the death case of two students due to ‘klitih’ acts happened at SMP Piri I Yogyakarta. The phenomenon of ‘klitih’ is interesting as it closely related to the problem of character education. For that, this research focus on the efforts of the headmaster and teachers at SMP Piri I Yogyakarta in building love of peace character in the school by examining the leadership type of the headmaster, teachers exemplary, and the efforts of character building initiated by the school. By using qualitative approach, the data was gathered using indepth interview, observation, and documentation. This research finds that: first, the headmaster’s leadership type is democratic paternalistic. Second, love of peace character was build though teacher exemplary behavior using discipline, and the implementation of 5 S concept, they are salam (regards), senyum (smile), sapa (greet), sopan (polite), and segan (humble). Third, students character building was conducted by using heart, honor, tolerance, empathy, and justice. Those character is build together by all school’s community with eclectic method.